A strategy for monitoring systemic vulnerability to marine erosion and flooding - Catherine Meur-Ferec; Iwan Le Berre; Lucie Cocquempot; Élisabeth Guillou; Alain Henaff; Thibaud Lami; Nicolas Le Dantec; Pauline Letortu; Manuelle Philippe (Développement Durable et Territoires)
Littoralisation, or the concentration of people and activities in coastal areas, associated with the intrinsic mobility of coasts and with the context of climate change, tends to increase the vulnerability of coastal areas. This article presents a new interdisciplinary approach towards the concept of vulnerability that makes it possible to move beyond the nature/society dichotomy, and an inter-sectorial researcher-manager method for the development of a series of monitoring indicators for the four components of systemic vulnerability: hazards, stakes, management and representations. These indicators are precursors of an integrated observatory that will act as a source of data for research and inform public policy for coastal areas.